Time-motion characteristics and physiological responses of small-sided games in elite youth players: The influence of player number and rule changes - Hill-Haas, S. V; Coutts, A. J; Dawson, B. T.; Rowsell, G. (The Journal of Strength and Conditioning Research, 2010)
The aim of this study was to examine acute physiological responses and time-motion characteristics associated with 4 soccer-specific small-sided game (SSG) formats (3 vs. 4 players, 3 vs. 3 players + floater, 5 vs. 6 players, and 5 vs. 5 players + floater) and 4 rule changes in elite youth soccer players. Sixteen male youth soccer players (mean ± SD: age = 15.6 ± 0.8 years, stature = 170.8 ± 6.6 cm, body mass = 67.5 ± 6.2 kg, and 20-m shuttle run estimated VO2max = 57.4 ± 3.7 ml/kg·min) participated in the study, in which heart rate (HR), rating of perceived exertion (RPE), blood lactate (La-), and time-motion characteristics were recorded. The rule change requiring extra sprint running had a greater effect on the time-motion characteristics than all other rule modifications but no effect on acute %HRmax, La-, and RPE. Rule changes had no effect on RPE. Fixed underload teams (i.e., lower number of players compared with the opponent team) recorded a significantly higher RPE compared with the fixed overload teams, although there were no differences in %HRmax and La-. The major practical findings are that subtle changes in SSGs playing rules can influence the physiological, perceptual, and time-motion responses in young elite soccer players. Rules that are related to a team's chances of scoring may improve player motivation and thereby increase training intensity during SSGs. There were no differences between fixed and variable formats in terms of physiological and perceptual responses, although both may provide useful technical-tactical training. Coaches should take care in designing different soccer SSGs as each rule or game format change may influence exercise intensity independently.